Design and Development of Hybrid Hydrogels for Biomedical Applications: Recent Trends in Anticancer Drug Delivery and Tissue Engineering - Cai, Mao-Hua; Chen, Xiao-Yi; Fu, Luo-Qin; Du, Wen-Lin; Yang, Xue; Mou, Xiao-Zhou; Hu, Pei-Yang (Frontiers in Bioengineering and Biotechnology, 2021)
The applications of hydrogels in biomedical field has been since multiple decades. Discoveries in biology and chemistry render this platform endowed with much engineering potentials and growing continuously. Novel approaches in constructing these materials have led to the production of complex hybrid hydrogels systems that can incorporate both natural and synthetic polymers and other functional moieties for mediated cell response, tunable release kinetic profiles, thus they are used and research for diverse biomedical applications. Recent advancement in this field has established promising techniques for the development of biorelevant materials for construction of hybrid hydrogels with potential applications in the delivery of cancer therapeutics, drug discovery, and re-generative medicines. In this review, recent trends in advanced hybrid hydrogels systems incorporating nano/ microstructures, their synthesis, and their potential applications in tissue engineering and anticancer drug delivery has been discussed. Examples of some new approaches including click reactions implementation, 3D printing, and photopatterning for the development of these materials has been briefly discussed. In addition, the application of biomolecules and motifs for desired outcomes, and tailoring of their transport and kinetic behavior for achieving desired outcomes in hybrid nanogels has also been reviewed.